2017
DOI: 10.1371/journal.pone.0179654
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic microvascular dysfunction and increased advanced glycation end products are components of non-alcoholic fatty liver disease

Abstract: BackgroundThis study aimed to investigate the pathophysiology of hepatic microcirculatory dysfunction in non-alcoholic fatty liver disease (NAFLD).MethodsIn Wistar rats, NAFLD model was induced by 20 weeks of high-fat diet (HFD) feeding. Rolling and adhesion of leukocytes and tissue perfusion in hepatic microcirculation were examined using in vivo microscopic and laser speckle contrast imaging (LSCI), respectively. Oxidative stress and inflamatory parameters were analysed by TBARs, catalase enzyme activity, RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 58 publications
5
68
0
3
Order By: Relevance
“…noted that regular moderate training in humans appears beneficial for oxidative stress and health, conversely, acute exercise leads to increased oxidative stress (22), presumably as their a period of adaptation that is missing from acute exercise training. Pereira et al also showed high-intensity exercise may induce oxidative stress (23). Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…noted that regular moderate training in humans appears beneficial for oxidative stress and health, conversely, acute exercise leads to increased oxidative stress (22), presumably as their a period of adaptation that is missing from acute exercise training. Pereira et al also showed high-intensity exercise may induce oxidative stress (23). Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences of glyceraldehyde 3‐phosphate dehydrogenase (GAPDH), IFN‐γ, and VCAM‐1 were synthesized by Metabion International. Primer sequences are: GAPDH forward 5′‐CCATTCTTCCACCTTTGATGCT‐3′, reverse 5′‐TGTTGCTGTAGCCATATTCATTGT‐3′; IFN‐γ forward 5′‐AACCAGGCCATCAGCAACAACA‐3′, reverse 5′‐ACCGACTCCTTTTCCGCTTCCT‐3′ and VCAM‐1 forward 5′‐GCGAAGGAAACTGGAGAAGACA‐3′, reverse 5′‐ACACATTAGGGACCGTGCAGTT‐3′ …”
Section: Methodsmentioning
confidence: 99%
“…Advanced glycation end-products (AGE) accumulate in metabolic disorders, such as hepatic steatosis, which is the initiating condition in ALD. Plasma AGEs increase markedly in patients with end-stage liver disease, indicating the important role of the liver in catabolizing AGEs [31]. Uptake of AGE in liver endothelial, Kupffer, and parenchymal cells accounted for roughly 60%, 25%, and 10%-15%, respectively, of hepatic elimination [31].…”
Section: Decreased Age Receptor Expression With Synbiotic Supplementamentioning
confidence: 99%
“…Plasma AGEs increase markedly in patients with end-stage liver disease, indicating the important role of the liver in catabolizing AGEs [31]. Uptake of AGE in liver endothelial, Kupffer, and parenchymal cells accounted for roughly 60%, 25%, and 10%-15%, respectively, of hepatic elimination [31]. Since we previously reported that synbiotic supplementation protected against hepatic steatosis and markers of oxidative stress [14], we analyzed liver sections in mice for the protein expression of receptors for AGE (RAGE) and galectin-3 by immunostaining and immunoblotting.…”
Section: Decreased Age Receptor Expression With Synbiotic Supplementamentioning
confidence: 99%
See 1 more Smart Citation